An ecological risk assessment model for Arctic oil spills from a subsea pipeline - Ehsan Arzaghi; Abbassi, R; Vikrambhai Garaniya; Jonathan Binns; Faisal Khan (2018)
There is significant risk associated with increased oil and gas exploration activities in the Arctic Ocean. This paper presents a probabilistic methodology for Ecological Risk Assessment (ERA) of accidental oil spills in this region. A fugacity approach is adopted to model the fate and transport of released oil, taking into account the uncertainty of input variables. This assists in predicting the 95th percentile Predicted Exposure Concentration (PEC 95% ) of pollutants in different media. The 5th percentile Predicted No Effect Concentration (PNEC 5% ) is obtained from toxicity data for 19 species. A model based on Dynamic Bayesian Network (DBN) is developed to assess the ecological risk posed to the aquatic community. The model enables accounting for the occurrence likelihood of input parameters, as well as analyzing the time-variable risk profile caused by seasonal changes. It is observed through the results that previous probabilistic methods developed for ERA can be overestimating the risk level.